Dorestad in an international Framework - Willemsen, Annemarieke; Kik, H. (Brepols, 2010)
Dorestad is a large, wealthy and internationally orientated harbour town from the Carolingian era excavated at the site of Wijk bij Duurstede in the middle of the Netherlands. In the 8th and 9th century AD it functioned as a junction in a network of Carolingian <span class=